Pesantren Resilience: The Path to Prevent Radicalism and Violent Extremism - Abubakar, Irfan; Hemay, Idris (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2020)
The phenomena of radicalism and violent extremism in Indonesia, in some cases, cannot be separated from pesantren (Islamic boarding schools); some jihadis (read: terrorists) are pesantren graduates. However, as an educational institution that has rooted in the Indonesia Muslim communities, the majority of pesantren carry the spirit of religious moderation. They have even produced many alumni promoting peaceful, tolerant, and democratic views of Islam. Some pundits have confirmed the moderate character of pesantren. Azyumardi Azra, in his review on the results of the study of the Center for the Study of Religion and Culture (CSRC) and the Center for the Study of Islam and Society (PPIM, Pusat Pengkajian Islam dan Masyarakat) UIN Jakarta (The Jakarta Post, 22 December 2019), underlines that pesantren has contributed to fostering the understanding of moderate Islam (wasaṭīyah). Pesantren is different from Islamic educational institutions in other Muslim countries, such as Pakistan, Yemen, Afghanistan, etc. In those countries, many madrasahs (Islamic schools) become a place of a breeding ground for a radical understanding of Islam. The CSRC and PPIM UIN Jakarta’s study (2019) shows that pesantren has “social resilience” which can hinder them from the influence of radical ideology, although they still have some vulnerabilities. Pesantren resilience is resulted by their capacity in empowering their social capitals that have been existed in three social connectivity: social bonding, social bridging, and social linking.